2016
DOI: 10.1021/acs.jpcc.5b11768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkaline Earth Metal Amides on Ru in Catalytic Ammonia Decomposition

Abstract: The effects of alkaline earth metal amides (Mg­(NH2)2, Ca­(NH2)2, and Ba­(NH2)2) on Ru in catalyzing NH3 decomposition were investigated. The catalytic activities rank in the order of Ru–Ba­(NH2)2 > Ru–Ca­(NH2)2 > Ru–Mg­(NH2)2, among which Ru–Ba­(NH2)2 and Ru–Ca­(NH2)2 catalysts have higher intrinsic activities (TOF) and lower apparent activation energies than those of Ru–Mg­(NH2)2 and Ru/MgO catalysts, indicating that Ca­(NH2)2 and Ba­(NH2)2 may have different roles from those of Mg­(NH2)2 and MgO. The TPR (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 49 publications
3
45
1
2
Order By: Relevance
“…The decomposition of NH 3 over Rb 2 [Mn(NH 2 ) 4 ] and K 2 [Mn(NH 2 ) 4 ] starts at around 350 °C, which is close to the main appearance temperature of N 2 and H 2 in the Ar‐TPR spectra (Figure d). This ammonia decomposition temperature is similar to those of the noble metal catalysts for ammonia decomposition . At 500 °C, both amide systems show good NH 3 decomposition properties.…”
Section: Figuresupporting
confidence: 69%
See 2 more Smart Citations
“…The decomposition of NH 3 over Rb 2 [Mn(NH 2 ) 4 ] and K 2 [Mn(NH 2 ) 4 ] starts at around 350 °C, which is close to the main appearance temperature of N 2 and H 2 in the Ar‐TPR spectra (Figure d). This ammonia decomposition temperature is similar to those of the noble metal catalysts for ammonia decomposition . At 500 °C, both amide systems show good NH 3 decomposition properties.…”
Section: Figuresupporting
confidence: 69%
“…At this temperature, the NH 3 decomposition conversions of Rb 2 [Mn(NH 2 ) 4 ] and K 2 [Mn(NH 2 ) 4 ] reach 68 % and 48 %, respectively. These NH 3 decomposition conversions are much higher than that of MnN (15 %) and similar to that of Ru/MgO catalyst under the same reaction conditions. Similar phenomena were found in the previous results using composite catalysts composed of MnN and NaNH 2 /KNH 2 .…”
Section: Figuresupporting
confidence: 64%
See 1 more Smart Citation
“…These kinetic analyses suggest that ammonia decomposition over Ru/Ca(NH 2 ) 2 proceeds by the same reaction mechanism as with conventional Ru catalysts, that is, the Temkin–Pyzhev mechanism, in which the recombinative desorption of N adatoms from the metal surface dominates the ammonia decomposition rate. This result is significantly different from that of Yu et al., who reported that Ru/Ba(NH 2 ) 2 and Ru/Ca(NH 2 ) 2 have higher TOF and lower activation energy than Ru/MgO. Furthermore, they postulated a new reaction mechanism in which the decomposition of amides by the Ru catalyst to form N 2 and H 2 is the rate‐determining step of ammonia decomposition.…”
Section: Resultscontrasting
confidence: 69%
“…Furthermore, Guo et al . and Yu et al . reported ammonia decomposition by catalysts combining Ru particles and metal amides such as LiNH 2 –Ru/MgO and Ru/AE(NH 2 ) 2 (AE=Mg, Ca, Ba).…”
Section: Introductionmentioning
confidence: 99%